Morphological characterization of greengram (Vigana radiata) varieties and their application for distinctness, uniformity and stability testing - Katiyar, P K; Dixit, G P; Singh, B B (The Indian Journal of Agricultural Sciences, 2008)
A study was carried during 2004-06 on morphological characterization of greengram [Vigna radiata (L.) Wilezek] and establish distintness of the candidate variety from all other varieties. A total of 73 released Indian cultivars of greengram were grouped for several agromorphological descriptors. The anthocyanin colour was present in all varieties except in ’Pant M 3’, ’OBGG 52’, ’RWG 344’, ’COGG 912’ and ’HUM 12’. The stem colour was generally green or greenish with purple splashes except in ’AKM 8802’ which depicted purple colour. Wide diversity (38 to 70 cm) has been observed in plant height. Shiny seed lusture was observed in ’IPM 99-125 (Meha)’, ’GM 3’, ’Asha’, ’MUM 2’, ’Samrat (PDM 139)’, ’PDM 11’, ’Pusa 105’, ’PS 16’, ’RMG 268’, ’Sujata’ and ’Sona’. All the greengram varieties are green in seed colour except ’Sona’ which is yellow in colour. Maximum varieties are of medium seed size (3-5 g/100-seed weight) except ’Pusa Vishal’ and ’SML 668’ (large seeded &gt 5 g/100 seed). Such characterization of released cultivars will provide valuable information for the strengthening of further breeding programme in greengram.